BUSINESS ANALYSIS OF PROCESSED JELLYFISH PRODUCTS AS A TRADITIONAL SOUVENIR FROM PALOH - Nur Istiqamah; Nur Astri Fatihah; Muslimah (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2026)
The local community has not yet fully utilised the potential of the marine resources in Paloh Sub-district, specifically jellyfish. In addition to the high volume of jellyfish caught in the area, Paloh Sub-district's tourist attractions are always bustling with visitors. However, despite the tourism potential, there is a lack of distinctive souvenirs for tourists to take home. This presents a business opportunity for suppliers of distinctive Paloh souvenirs. Field data from this study indicate that, during the season from around February to April, processing plants in Paloh Sub-district can yield 10–40 tonnes of processed jellyfish. These products are hard to find elsewhere, making them a potential signature souvenir for Paloh Sub-district. Preserved processed jellyfish, packaged in small containers, represent an innovative, affordable product that is easy for tourists to carry. The product has a shelf life of 1–2 years. A business analysis of the jellyfish processing venture indicates that it is viable. The feasibility analysis shows total costs of IDR 1,580,000, revenue of IDR 3,150,000, a profit of IDR 1,570,000, an R/C ratio of 2.006, a production BEP of 45.14 packs, and a price BEP of IDR 17,555.6.